Gap between Regions in the Use of E-Commerce by MSEs: Macro-level Research Using Provincial Data from Indonesia - Busnetti, Ida; Tambunan, Tulus (Journal of Telecommunications and the Digital Economy, 2020)
The availability of information and communication technology (ICT) has assisted companies to effectively produce and market their products and services in the global market. However, the majority of micro and small enterprises (MSEs) in Indonesia have not adopted such technology or e-commerce to support their business activities. Based on province data (cross-section data), this study aims to examine the adoption of e-commerce by MSEs in different provinces in Indonesia. It addresses two research questions. First, how many MSEs have adopted such technology? Second, what factors influence e-commerce adoption by MSEs? The study used multiple regression to estimate empirically the impact of selected factors as independent variables on the number of MSEs that use e-commerce. It shows at least three important facts: (i) the degree of e-commerce adoption by MSEs in Indonesia is still very low; (ii) there is a positive relationship between market size in a province and the number of MSEs in the province adopting e-commerce; and (iii) in a region where all residents or households have a computer or access to the Internet, it is not always that all business actors, especially MSEs, in that region adopt e-commerce.